2023
DOI: 10.1007/s00592-023-02047-6
|View full text |Cite
|
Sign up to set email alerts
|

Previous induced abortion or miscarriage is associated with increased odds for gestational diabetes: a nationwide register-based cohort study in Finland

Abstract: Aims The aim of this study was to investigate the association between previous induced abortion or miscarriage and the development of gestational diabetes mellitus (GDM) using high-quality register data. Methods In this retrospective nationwide register-based cohort study, data from the national medical birth register (MBR) were used to evaluate the association between a history of miscarriage or induced abortion and GDM. We included all first pregnancies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
(15 reference statements)
1
3
0
Order By: Relevance
“…In the meta-analysis done by Wang et al, they included 31 studies with 311,900 subjects and compared GDM to non-GDM mothers where they found the prevalence of lost parity was higher in mothers with GDM and thus concluded that the occurrence of fetal loss is significant for the occurrence of GDM. 15 Similar findings were identified by Zhao et al and Vaajala et al 16,17 The majority of the mothers, 57 (72.15%) were on a diabetic diet. This is a common diabetic control method recommended by several guidelines for the control of diabetes in pregnancy.…”
Section: Discussionsupporting
confidence: 75%
“…In the meta-analysis done by Wang et al, they included 31 studies with 311,900 subjects and compared GDM to non-GDM mothers where they found the prevalence of lost parity was higher in mothers with GDM and thus concluded that the occurrence of fetal loss is significant for the occurrence of GDM. 15 Similar findings were identified by Zhao et al and Vaajala et al 16,17 The majority of the mothers, 57 (72.15%) were on a diabetic diet. This is a common diabetic control method recommended by several guidelines for the control of diabetes in pregnancy.…”
Section: Discussionsupporting
confidence: 75%
“…For women who had a prior IA, 17 , 30 , 33 , 59 , 60 there was a small increased risk of gestational diabetes mellitus in subsequent pregnancies, with effects ranging from aOR 1.03 (95% CI 0.97–1.10) 59 to aOR 1.18 (95% CI 1.12–1.24). 17 Three studies 17 , 59 , 60 were included in a meta-analysis, producing a pooled aOR of 1.04 (95% CI 0.97–1.12, I 2 = 89.6%), indicating that women who had a prior IA did not have increased odds of developing gestational diabetes mellitus in subsequent pregnancy ( Supplementary Figure S1 ). Of the six studies 41 , 42 , 45 , 48 , 62 , 75 that examined the association between RPL and gestational diabetes mellitus effects ranged from an aOR of 0.69 (95% CI 0.47–1.02) to aOR 1.69 (95% CI 1.10–2.59).…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies were marked as high risk of bias, six 41 , 42 , 43 , 44 , 45 , 46 of which failed to control for adequate confounding variables and four 47 , 48 , 49 , 50 which failed to sufficiently define their exposure variables. 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 Thirteen studies 14 , 17 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 were deemed to be of moderate risk of bias, with 16 studies deemed to be of low risk of bias 16 , 18 , 33 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ( Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation